2014
DOI: 10.5194/bgd-11-7931-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanisms of microbial carbon sequestration in the ocean – future research directions

Abstract: Abstract. This paper reviews progress on understanding biological carbon sequestration in the ocean with special reference to the microbial formation and transformation of recalcitrant dissolved organic carbon (RDOC), the microbial carbon pump (MCP). We propose that RDOC is a relative concept with a wide continuum of recalcitrance. Most RDOC compounds maintain their levels of recalcitrance only in a specific environmental context (RDOCt). The ocean RDOC pool also contains compounds that may be inaccessible to … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 210 publications
(202 reference statements)
3
61
0
1
Order By: Relevance
“…With the FT‐ICR‐MS analysis, the overall properties of the residual SDOM indicate that the SDOM was microbially modified to a higher unsaturated state and likely containing more aromatic rings in molecules, these properties of residue SDOM are similar to the properties of deep‐sea RDOM (Catalá et al, ; Flerus et al, ; Hertkorn et al, ; Lechtenfeld et al, ; Li et al, ; Medeiros et al, ). The chemical changes of DOM properties (Table ) combined with the succession of microbial community (Figure b) observed in our study might reflect the generation of RDOM via the microbial carbon pump (Jiao et al, ), which proposes that the microbial successive processing on labile DOM generates long‐lived RDOM in the water column (Jiao et al, ; Jiao et al, ). Our SDOM incubation experiment suggests that the microbial mediated RDOM may contribute to the autochthonous recalcitrant carbon in coastal environments (Asmala et al, ), which could be subjected to further cycling through biotic and abiotic processes in the ocean.…”
Section: Resultssupporting
confidence: 50%
“…With the FT‐ICR‐MS analysis, the overall properties of the residual SDOM indicate that the SDOM was microbially modified to a higher unsaturated state and likely containing more aromatic rings in molecules, these properties of residue SDOM are similar to the properties of deep‐sea RDOM (Catalá et al, ; Flerus et al, ; Hertkorn et al, ; Lechtenfeld et al, ; Li et al, ; Medeiros et al, ). The chemical changes of DOM properties (Table ) combined with the succession of microbial community (Figure b) observed in our study might reflect the generation of RDOM via the microbial carbon pump (Jiao et al, ), which proposes that the microbial successive processing on labile DOM generates long‐lived RDOM in the water column (Jiao et al, ; Jiao et al, ). Our SDOM incubation experiment suggests that the microbial mediated RDOM may contribute to the autochthonous recalcitrant carbon in coastal environments (Asmala et al, ), which could be subjected to further cycling through biotic and abiotic processes in the ocean.…”
Section: Resultssupporting
confidence: 50%
“…Another explanation for the long‐term persistence of RDOC is the structural recalcitrance of the molecules in a specific environmental context, which corresponds to the previously proposed concept of biologically inert RDOC (RDOC t ) (Jiao et al ., ). This idea is supported by the evidence that the chemical composition of the DOC in the deep ocean, where the RDOC dominates, is different from that of decomposable DOC (Jannasch, ; Lancelot et al ., ; Kaiser and Benner, ; Jiao et al ., ; Benner and Amon, ; Walker et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…A DOC pool that persists over millennial timescales in the deep ocean is central to the concept of the “microbial carbon pump” (MCP) [ Jiao et al , , ]. Similar to the solubility, soft‐tissue, and carbonate pumps that maintain a vertical gradient of DIC and alkalinity in the ocean against erosion by ocean circulation [ Volk and Hoffert , ], the MCP is posited to maintain a gradient of DOC from short‐lived, highly reactive DOC in the surface ocean to longer‐lived, less reactive DOC in the deep ocean [ Legendre et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…Dilution and recalcitrant molecular structures are not mutually exclusive hypotheses. Jiao et al [] recognize that DOC in the deep ocean may be composed of both a fraction that is intrinsically recalcitrant and a fraction that is bioavailable but cannot be degraded due to its low concentration. Jiao et al [] alternatively suggest that bacterial growth observed in Arrieta et al [] was supported by a smaller bioavailable DOC fraction that was either present in the original DOC sample or was produced by processes such as viral lysis, chemolithoautotrophic activities, or grazing during the experiment rather than a release from dilution by enrichments.…”
Section: Introductionmentioning
confidence: 99%